Marketing With Emotional Branding: A Case Study on English Courses in Kampung Pare - M Bambang Purwanto; Vivin Afini; Ridayani; Roberto Aldy Ratoeloedji (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research raises a crucial issue related to the importance of emotional branding in increasing consumer loyalty in English courses. In an increasingly fierce competition era, consumers seek educational services and meaningful emotional experiences. The problem identified was the low emotional engagement provided by the course institution, thus affecting customer loyalty. This study aims to analyze elements of emotional branding, such as brand stories, the use of emotional language, and sensory experiences in creating an emotional connection with consumers. The research method uses a qualitative approach with a demographic study design. Data was collected through in-depth interviews, observations, and analysis of promotional documents. The results show that elements of brand stories and sensory experiences significantly increase emotional attachment and consumer loyalty. This study concludes that emotional branding is a key strategy for building long-term relationships with consumers in the education sector.